2017
DOI: 10.1016/j.envres.2017.06.019
|View full text |Cite|
|
Sign up to set email alerts
|

Per- and polyfluoroalkyl substances in plasma and feathers of nestling birds of prey from northern Norway

Abstract: Plasma samples from nestlings of two top predators, White-tailed eagle (Haliaeetus albicilla) and Northern goshawk (Accipiter gentilis) from northern Norway were analysed for a wide range of per- and polyfluoroalkyl substances (PFASs). Body feathers from the White-tailed eagles were also analysed and significant associations between specific PFASs in blood plasma and body feathers were found (0.36 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 63 publications
10
23
1
Order By: Relevance
“…The concentration profile with high concentrations in the preen oil was expected due to the high lipid content of the oil and the lipophilic nature of these compounds (Eulaers et al, 2011b). The concentrations of the main contaminant contributors (CB 153,p,BDE 47 and PFUnA, Table 1) in plasma, feathers and preen oil were slightly lower in the current study than previously reported in white-tailed eagle nestlings from Norway (Eulaers et al, 2011a(Eulaers et al, , 2011b(Eulaers et al, , 2014Gómez-Ramírez et al, 2017). The samples from the previous studies were collected in 2008, 2009, 2011 and 2014, and some also at other locations than Smøla and…”
Section: Detection Frequencies and Concentrations Of Legacy Pops And Ecscontrasting
confidence: 63%
See 4 more Smart Citations
“…The concentration profile with high concentrations in the preen oil was expected due to the high lipid content of the oil and the lipophilic nature of these compounds (Eulaers et al, 2011b). The concentrations of the main contaminant contributors (CB 153,p,BDE 47 and PFUnA, Table 1) in plasma, feathers and preen oil were slightly lower in the current study than previously reported in white-tailed eagle nestlings from Norway (Eulaers et al, 2011a(Eulaers et al, , 2011b(Eulaers et al, , 2014Gómez-Ramírez et al, 2017). The samples from the previous studies were collected in 2008, 2009, 2011 and 2014, and some also at other locations than Smøla and…”
Section: Detection Frequencies and Concentrations Of Legacy Pops And Ecscontrasting
confidence: 63%
“…Data were treated in the same way as in most previous studies on bird feathers and preen oil to allow for direct comparison (i.e. Eulaers et al, 2011a, 2011b, Gómez-Ramírez et al, 2017. Thus, compounds quantified in over 50 % of samples and detected in both feathers and plasma samples within each location and each year were included in the statistical analyses.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 3 more Smart Citations